Decision Support System for Permanent Employee Selection at PT XYZ with Moora Method - Bagas Setiyaki Wicaksono; Budi Apriyanto; Azhar Fathoni (International Journal of Integrated Science and Technology, 2024)
Using the multi-objective optimization method based on ratio analysis (MOORA), the purpose of this research is to develop a decision support system that will help the selection process of permanent employees at PT XYZ. In order to improve the productivity and operational efficiency of the company, a proper employee selection process is essential. Nonetheless, many factors influence the decision taken, which is often subjective. Therefore, a systematic approach is needed to help managers assess and select potential employees based on predefined standards. The MOORA method was chosen because it is able to provide optimal solutions for a variety of different criteria. The identification of employee selection criteria, the collection of employee candidate data, and the use of the MOORA method to generate employee candidate rankings are all actions performed in this study. The criteria used include work experience, education The purpose of this research is to create a system that supports the process, skills, and attitudes in decision making. The results of this system show that MOORA has the ability to provide more objective and transparent recommendations in the employee selection process than conventional methods.  The results of the analysis show that this system helps decision making and increases managers' confidence in choosing employees who match the company's needs. PT XYZ hopes to use this decision support system to reduce errors in the employee selection process and help achieve the company's strategic goals. It is hoped that this research will help the process of developing decision support systems in the field of human resources.